2015
DOI: 10.1038/srep09476
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ubiquitin inhibits the proliferation and radioresistance of non-small cell lung cancer cells in vitro and in vivo

Abstract: Radioresistance has been an important factor in restricting efficacy of radiotherapy for non-small cell lung cancer (NSCLC) patients and new approaches to inhibit cancer growth and sensitize irradiation were warranted. Despite the important role of ubiquitin/proteasome system (UPS) during cancer progression and treatment, the expression and biological role of ubiquitin (Ub) in human NSCLC has not been characterized. In this study, we found that ubiquitin was significantly overexpressed in 75 NSCLC tissues, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 51 publications
(57 reference statements)
7
55
0
Order By: Relevance
“…For instance, the expression of enolase 1, cytokeratin 18 and HSPs in tumors may be valuable diagnostic and therapeutic targets. Overexpression of ubiquitin C in this study corroborates a previous research that found down-regulation of ubiquitin C suppresses growth and increases the radio-sensitivity of human nonsmall cell lung carcinoma cells (18). Interestingly, three of the shared genes are related to the HSP family, suggesting their Original Article possible involvement in cancer progression.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, the expression of enolase 1, cytokeratin 18 and HSPs in tumors may be valuable diagnostic and therapeutic targets. Overexpression of ubiquitin C in this study corroborates a previous research that found down-regulation of ubiquitin C suppresses growth and increases the radio-sensitivity of human nonsmall cell lung carcinoma cells (18). Interestingly, three of the shared genes are related to the HSP family, suggesting their Original Article possible involvement in cancer progression.…”
Section: Discussionsupporting
confidence: 89%
“…After 24 h, the cells were transfected with 50 nM of SPINK13-overexpressing vector (pcDNA-SPINK13), control vector (pcDNA3.1), siRNA-SPINK13 (si-SPINK13) or siRNA-NC (si-NC) and allowed to grow for another 48 h. Cell proliferation was measured using the MTT assay as reported previously [18]. The OD value was represented as the viability index.…”
Section: Methodsmentioning
confidence: 99%
“…Among the 10 hub DMGs revealed in our analysis, six (STAT3, PTPN6, SYK, STAT5B,and XPO1, and ABL1) had known CLL relevance; hence, our results corroborated previous data. The remaining four (UBC, GRB2, CREBBP, and GAB2) have never been reported in previous CLL studies [38][39][40][41][42][43][44][45][46][47][48] . UBC represents a ubiquitin gene (ubiquitin C) and has been described in cancers infrequently.…”
Section: Discussionmentioning
confidence: 73%